The role of radicalism and extremism in political terrorism - Muhić, Emir (Technium Social Sciences Journal, 2021)
The world changed significantly and abruptly after September 11, 2001, when the largest terrorist attack in the known history of mankind was carried out. The attack marked a new era in the use of violence and fear to secure specific political goals. However, as time goes on, conventional killer forms of terrorism are no longer as effective and efficient as before, and other, unconventional forms of violence are being used. As one such novelty, political terrorism is emerging whose goal is not to kill, but to spread fear among targeted communities and groups. Political terrorism has its place in the post-conflict, transitional societies and nations as those in the Balkans, where it is not possible to conduct kinetic activities due to the threat of sanctions. Therefore, aggressive actors resort to the use of fear to achieve political goals, but this would not be possible without two very important socio - political factors: radicalism and extremism which provide support to political actors who strive to create ethnically and nationally ’pure’ territories without entering into open conflict and war. Also, radicalism and extremism are weapons of support for political terrorism that rejects the use of conventional violence and kinetic measures, but creates a hostile environment and climate that forces victims to submit or leave their homes. Violation of democracy, human rights and freedoms, as well as making a normal way of life impossible - is the main goal of political terrorism, which could not be achieved without radicalization and extremization of a critical mass of followers of aggressive politics and its actors.